My fluid diary sebagai alternatif pencatatan asupan cairan harian: studi crossover pada remaja putri - Hiya Alfi Rahmah; Izka Sofiyya Wahyurin; Ajeng Dian Purnamasari; Farah Paramita (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2022)
My fluid diary as an alternative tool for daily recording fluid intake: cross over study among adolescent girlsBackground: Water plays a vital role in the human body. The respondents found the fluid intake record using paper-based excessively burdensome, so a smartphone-based application was developed as a drink intake recording tool.Objective: Assessing the validity of My Fluid Diary as a fluid intake recording tool using 7-day records as a reference method.Methods: A crossover study was conducted involving 38 female students of SMKN 1 Banyumas. Total water intake was recorded for seven days for each method (smartphone-based and paper-based), with 14 days washout period between the two methods. To determine the difference in water intake between the two methods, the Wilcoxon Signed Rank Test was used; Bland-Altman plots and linear regression tests were used to determine the agreement between the two methods; and the Spearman test was used to determine the relationship between water intake and hydration status.Results: Water intake was significantly higher with smartphone application-based recording than with paper-based recording (1008.3 (421.3 – 2363) and 763.2 (435 – 1875.5); p 0.0001), with agreement limit of 1, 11 – 3.00 and ß -value (0.296) p-value 0.05 in the regression test, indicating no fixed bias. The findings of recording water intake and hydration status were significantly correlated with the two methods (p-value<0,05). The Spearman correlation value shows a negative number in both ways with sufficient correlation strength (0.03 – 0.05).Conclusion: My Fluid Diary smartphone application could be used as an alternate tool for recording fluid intake based on the agreement and hydration status that has been studied. Further research is expected to involve more respondents.